(untitled) (Bioscience Journal, 2018)
The objective of this work was to select soybean genotypes with high yield, adaptability and stability in different sowing seasons in the Cerrado-Pantanal ecotone region using the MHPRVG method (harmonic mean of the relative performance of genetic values). We evaluated 10 soybean genotypes at two sowing seasons in Aquidauana/MS in the agricultural year 2014/2015. At maturation, the following agronomic traits were evaluated: plant height (PH), first pod height (FPH), number of branches per plant (NB), number of pods per plant (NP), number of grains per pod (NGP), mass of hundred grains (MHG) and yield grain (YIE). Likelihood ratio test detected significant genotype x seasons interaction only for grain yield. The genotypes AS3730, 97R73 and SYN9070 showed high adaptability and can be growing in both sowing seasons in the Cerrado/Pantanal ecotone. The genotypes 97R21 and B4184 have high phenotypic stability and are indicated for growing in later sowing season.